Realization of the Right to Self-determination in the Framework of R2P - Mohsen Abdollahi; Seyed Reza Hosseini (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2023)
Introduction The right to self-determination could be applied in situations aiming to prevent crimes against humanity that are subject to the responsibility to protect. Generally, governments that violate the right to self-determination of their people, including minority groups, are more prone to committing these heinous crimes. The doctrine of the responsibility to protect seeks to establish a responsible government toward its citizens; The protection aspect of the doctrine has been discussed in this research, which does not necessarily include intervention. Adhering to human rights standards and exercising the right to self-determination in the framework of the responsibility to protect is a foundation to prevent situations that can lead to atrocities and widespread violations of human rights. Thus, this can be considered as the link between the right to self-determination and the responsibility to protect. Literature ReviewThe right to self-determination of people has been an important subject of much legal research as a fundamental principle of international law. On the other hand, the responsibility to protect is also among the attractive topics of international law as a new doctrine. The two notions have been separately discussed by researchers such as Antonio Cassese, Jörg Fisch, Yasmine Nahlawi, and Stacey Henderson.It can be claimed that the subject of this article which is an updated version of the corresponding author’s master’s thesis, is an innovative topic in the international law literature and has not been explored before.  MethodologyFirstly, a descriptive research method has been used for this research i.e., the characteristics and aspects of the right to self-determination and the responsibility to protect have been discussed separately. Secondly, based on the legal research method, the governments’ experiences in different situations have been observed to reach the final research result regarding the commonalities of these two notions. ResultsFrom the international law’s point of view, the internal aspect of the right to self-determination is an erga omnes rule, and its external dimension has been accepted as a jus cogens rule.However, it should be noted that a separatist interpretation of the right to self-determination has no place in the current system of international law. International legal doctrines, governments’ stances, and international documents always emphasize on the importance and priority of the principle of territorial integrity. Further, international peace and security requires that separatist interpretations not be supported.  ConclusionToday, respecting human rights and, most importantly, the right to self-determination is a global matter and the international community should contribute to its realization. The right to self-determination can be realized indirectly under the doctrine of responsibility to protect. In other words, the right to self-determination can be applied as a means of preventing the occurrence of crimes that are subject to the responsibility to protect doctrine, and in this regard, the international community can assist and take measures and put them on its agenda to ensure the exercise of this right.The responsibility to protect emphasizes the primary responsibility of governments and the international community to assist other countries in carrying out their sovereign duties and only refers to the element of intervention at the last stage. the international community should come to the understanding that non-interventionist measures and international aid to the governments have a fundamental role and importance in supporting people and strengthening them and are to the benefit of international peace and security. The application of the responsibility to protect in Libya and the remedial secession in Kosovo showed how ineffective and destructive under-developed legal theories can be in practice.On the other hand, the doctrine of responsibility to protect suffers from a lack of clear criteria for intervention which is a problem that the international community should take steps to resolve. In many cases, powerful countries, especially the permanent members of the Security Council, apply double standards towards human rights issues. So, in order to prevent similar tragedies and protect the citizens, the international community should set clear and thorough standards regarding human rights issues and make them binding. However, it should be noted that the concept of cultural diversity should be taken into account In the process of formulating standards because, in issues related to human rights, no fixed standard that could be applied to all.